(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ernilasari, Walil K, Fitmawati, Roslim DI, Zumaidar, Saudah, Rayhannisa. 2021. Antibacterial activity of leaves, flowers, and fruits extract of Etlingera elatior from Nagan Raya District, Indonesia against Escherichia coli and Staphylococcus aureus. Biodiversitas 22: 4457-4464. Etlingera elatior is a medicinal plant that has been used by people in Indonesia, especially Acehnese people. Based on its secondary metabolites, E. elatior can be used as antibacterial agents against Gram-positive and Gram-negative. However, to determine the antibacterial activity of E. elatior, the parts of E. elatior that have been used are leaves, flowers, and fruits. This study was aimed to determine the best concentration of ethanol extract of leaves, flowers, and fruits of E. elatior as an inhibitor against Escherichia coli and Staphylococcus aureus. The extract was made by the maceration method with 70% ethanol as a solvent. Antibacterial activity test was carried out by the diffusion agar method using concentrations of 0.5%, 1%, 1.5% and 2%. The results showed that the fruit extract of E. elatior has antibacterial activity with an effective inhibitory zone at a concentration of 2% is 8.4 mm (E. coli) and 2.4 mm (S. aureus). Meanwhile, antibacterial activity the extract of leaves and flowers against E. elatior cannot determine yet. Identification of leaves, flowers and fruits extract of E. elatior using GC-MS (gas chromatography-mass spectroscopy) showed 56 compounds were detected.